2016
DOI: 10.1016/j.ijsu.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Management of venous ulcers: State of the art

Abstract: Venous ulceration is a complex and serious problem that affects 1-2% of the global elderly population (>65 years), and its incidence is constantly increasing. The population group with higher risk of development of venous ulceration is the elderly. These lesions have a significant negative impact on patients' quality of life. Our aim was to analyze the state of the art, starting with the medical literature review. The evidence supports that managing chronic wounds with a multidisciplinary wound care team signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 25 publications
1
19
0
5
Order By: Relevance
“…In this study, participants with UVE were mostly females and were between the sixth and seventh decade of life, which has been described in literature. (5,17) Marques (18) stated that female prevalence is due to gestational disorder that lead to post-thrombotic syndrome, besides the high prevalence of varicose veins, although some studies (10,19) described among their participants a proportion of UVE in men above 50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, participants with UVE were mostly females and were between the sixth and seventh decade of life, which has been described in literature. (5,17) Marques (18) stated that female prevalence is due to gestational disorder that lead to post-thrombotic syndrome, besides the high prevalence of varicose veins, although some studies (10,19) described among their participants a proportion of UVE in men above 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse risk factors have been described that favor the appearance of the wound; among them, those inherent to the physiopathology. (5)(6)(7) Fukaya and Margolis (8) consider, among others, immobility, obesity, rigidity of the ankle and deterioration of the calf muscle pump, which facilitate the appearance of varicose veins compromising blood irrigation systems. Some authors (9) hold that the most common factors are advanced age, family background of venous disease, increased body mass index, smoking, antecedents of traumatism, and prior venous thrombosis; they have also considered the patient's social history through characteristics of age, education, occupation, income, postural positions maintained, and access to care.…”
Section: Introduction Lmentioning
confidence: 99%
“…The lifetime risk of developing a venous leg ulcer is 1% 23. A recent retrospective cohort study using THIN (The Health Improvement Network) data reported that in the UK 53% of all venous leg ulcers healed within 12 months, with a mean healing time of three months 4.…”
mentioning
confidence: 99%
“…With demographic changes and a higher incidence of chronic ulcers, providers must consider increased treatment costs and nursing care. 8 , 10 , 11 In clinical practice, managing chronic infections is a key part of treating chronic wounds that requires a range of different products from antiseptics to specific dressings.…”
Section: Introductionmentioning
confidence: 99%